Analysis the clinical data from 51 colorectal cancer patients undergoing natural orifice specimen extraction surgery - Luo Jun; Wang gang; Liu yong; Zhu Yuping; Feng Haiyang (结直肠肛门外科)
[Objectives] To analyze the clinical data from colorectal cancer patients undergoing natural orifice specimen extraction surgery (NOSES) and explore the safety and oncological prognosis of NOSES. [Methods] A retrospective analysis was conducted on the clinical data of 51 patients with colorectal cancer who underwent NOSES at Zhejiang Cancer Hospital from January 2017 to July 2023. Surgical-related indicators, postoperative complications, pathological results and follow-up were analyzed, with survival analysis performed. [Results] Among the 51 patients, intraoperative blood loss was less than 100 mL in 34 patients (66.7%) and more than or equal to 100 mL in 17 patients (33.3%). The operation time averaged (185.5±74.3) minutes, and the mean number of lymph nodes obtained was (16.8±7.7). The tumor-to-anal margin distance was less than 5 cm in 36 patients (70.6%) and more than or equal to 5 cm in 15 patients (29.4%). Lesion diameter was less than 5 cm in 46 patients (90.2%) and more than or equal to 5 cm in 5 patients (9.8%). NOSES surgical methods included external excision in 11 patients (21.6%), pull-out excision in 23 patients (45.1%), and resection and traction in 17 patients (33.3%). Specimens were extracted from the rectum in 46 patients (90.2%) and through the vagina in 5 patients (9.8%). Protective colostomy was performed during the operation in 7 patients (13.7%). Postoperative recovery times were as follows: time to first flatus after surgery was 3 (3, 7) days, time to eat a semi-liquid diet after surgery was 7 (5, 8) days, and hospitalization time after surgery was 10 (8, 11) days. Postoperative complications included anastomotic leakage in 1 patient (2%), which healed well after conservative treatment; postoperative anastomotic bleeding in 1 patient (2%); and intestinal obstruction in 2 patients (3.9%), all of which were incomplete intestinal obstruction and improved after conservative treatment. Abdominal and pelvic infection occured in 3 patients (5.9%), urinary tract infection in 1 patient (2%), with no instances of abdominal and pelvic bleeding, bacteremia, pulmonary infection or unplanned second surgery. Postoperative pathological T staging revealed T0 in 3 patients, T1 in 9 patients, T2 in 17 patients, T3 in 11 patients, T4 in 11 patients. N staging included N0 in 39 patients, N1 in 11 patients, N2 in 1 patient. TNM staging showed stage 0 in 3 patients, stage Ⅰ in 20 patients, stage Ⅱ in 15 patients, stage Ⅲ in 11 patients, and stage Ⅳ in 2 patients. Differentiation revealed moderate to high differentiation in 45 patients and low differentiation and undifferentiation in 6 patients. Two patients had cancer nodes, 11 patients had vessel invasion, and 7 patients had nerve invasion. Follow-up concluded in August 2023, with a median follow-up time of 58 months (range from 1 to 76 months), and no patients were lost to follow-up. During the follow-up period, three patients developed recurrence and metastasis: two patients had distant metastasis before surgery and underwent radical surgery simultaneously, with liver recurrence at postoperative months 12 and 24, respectively; one patient had postoperative pathological TNM staging of Ⅱa, vessel and nerve invasion, with lung metastasis at postoperative months 27. One patient died, having had distant metastasis before surgery and undergoing radical surgery concurrently. Survival analysis was performed for all patients, revealing a five-year overall survival rate of 97.7% (95%CI 93.4%-100.0%) and a five-year disease-free survival rate of 93.5% (95% CI 86.3%-100%). [Conclusion] NOSES demonstrates good safety and short-term efficacy, in addition to a favorable oncological prognosis for the treatment of colorectal cancer.